An explanatory study of proxemics in relation to the perceptions of personal spaces of student boarders in shared bedrooms in selected boarding houses - Santuico, Mai-rim Nollaine N.; Florendo, Raquel Baltazar (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
This explanatory case study with a multi-method approach was undertaken to investigate the proxemics in relation to the perceptions of personal spaces of student boarders in shared bedrooms in selected boarding houses located at the Krus na Ligas area. This research aimed to determine how student boarders create their personal spaces in shared bedrooms based on the following: architectural and interior elements of space, spatial behavior of occupants, privacy and territoriality. It was also identified whether student boarders experience issues on privacy and territory and if there are, how would they address and resolve them. The perceptions of the student boarders were also classified in relation to the proxemics of their shared bedrooms. Data was elicited through semi-structured interviews involving twelve (12) informants who were purposely selected, site-observations and photo-documentation of four (4) chosen shared bedrooms which composed of two (2) 2-person rooms and two (2) 4-person rooms. Results had shown that the student boarders based their perceptions of their own areas on their basic needs and desired privacy. Furthermore, the informants? personal spaces established a sense of identity through their space organization and personal belongings. Instances of conflicts emerged from invasions of spaces but were resolved with minimal social interaction such as adjusting and complying one?s self with others. This suggested that relationships with other occupants were also considered to be a factor on the territorial and spatial behaviors of the informants. Lastly, the informants? needs of privacy were influenced and affected by the arrangement of furniture and the features of their personal spaces in their shared bedrooms.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Personal space; Personal space -- Human factors